Recent Advances Toward Highly Efficient Tandem Organic Solar Cells. Issue 1 (9th September 2020) - Xu, Xiaopeng; Li, Ying; Peng, Qiang
Abstract : Organic solar cells (OSCs) have attracted considerable attentions and have witnessed rapid progress from the aspects of material design, device engineering, and device physics. Tandem OSCs stacking more than one single‐junction device in series or parallel connection are developed to diminish the thermalization and/or transmission losses for improving the device performances. The optical managements by developing new photoactive materials, using high‐conductive semitransparent interconnecting layers and smart device architectures are the key factors toward high‐performance tandem OSCs. Herein, the recent advances in tandem OSCs are summarized from the aspects of photosensitive materials, interconnecting layers, and specific device structures. Finally, challenges and perspectives in the future development of tandem OSCs are also presented. Abstract : Herein, the development of tandem organic solar cells (OSCs) from the aspects of photosensitive materials, interconnecting layers and specific device structures is summarized. Challenges and perspectives of tandem OSCs in the future are also presented here.